Noise-induced hearing loss is correlated with alterations in the expression of GABAB receptors and PKC gamma in the murine cochlear nucleus complex - Kou, Zhen-Zhen; Qu, Juan; Li, Hui; Zhang, Dong-Liang; Li, Yun-Qing (Frontiers in Neuroanatomy, 2013)
Noise overexposure may induce permanent noise-induced hearing loss (NIHL). The cochlear nucleus complex (CNC) is the entry point for sensory information in the central auditory system. Impairments in gamma-aminobutyric acid (GABA)—mediated synaptic transmission in the CNC have been implicated in the pathogenesis of auditory disorders. However, the role of protein kinase C (PKC) signaling pathway in GABAergic inhibition in the CNC in NIHL remains elusive. Thus, we investigated the alterations of glutamic acid decarboxylase 67 (GAD67, the chemical marker for GABA-containing neurons), PKC γ subunit (PKCγ) and GABAB receptor (GABABR) expression in the CNC using transgenic GAD67-green fluorescent protein (GFP) knock-in mice, BALB/c mice and C57 mice. Immunohistochemical results indicate that the GFP-labeled GABAergic neurons were distributed in the molecular layer (ML) and fusiform cell layer (FCL) of the dorsal cochlear nucleus (DCN). We found that 69.91% of the GFP-positive neurons in the DCN were immunopositive for both PKCγ and GABABR1. The GAD67-positive terminals made contacts with PKCγ/GABABR1 colocalized neurons. Then we measured the changes of auditory thresholds in mice after noise exposure for 2 weeks, and detected the GAD67, PKCγ, and GABABR expression at mRNA and protein levels in the CNC. With noise over-exposure, there was a reduction in GABABR accompanied by an increase in PKCγ expression, but no significant change in GAD67 expression. In summary, our results demonstrate that alterations in the expression of PKCγ and GABABRs may be involved in impairments in GABAergic inhibition within the CNC and the development of NIHL.